Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1007/bf01977362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha-tocopherol and di-butyl-hydroxytoluene (BHT) on UV-A-induced photobinding of 8-methoxypsoralen to Wistar rat epidermal biomacromolecules in vivo

Abstract: The possible formation of singlet oxygen via photoexcited psoralens has been associated with the occurrence of, amongst others, erythema. Therefore it has been suggested to combine PUVA with the topical or systemic administration of antioxidants. However, the effect of these antioxidants on the photobinding of psoralens to DNA, which is held responsible for the anti-proliferative effect, should be taken into account. In the present study the effect of two phenolic antioxidants, alpha-tocopherol (AT) and butyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Vitamin E esters, particularly vitamin E acetate, were also shown to be promising agents in reducing UV-induced skin damage (Beijersbergen van Henegouwen et Bissett et al, 1990;Burke et al, 2000;Jurkiewicz et al, 1995;Record et al, 1991;Schoonderwoerd et al, 1991;Trevithick et al, , 1992. However, their photoprotective effects appear to be less pronounced as compared to vitamin E; as a result, some studies failed to detect photoprotection provided by vitamin E esters.…”
Section: Photoprotection Provided By Vitamin Ementioning
confidence: 91%
See 1 more Smart Citation
“…Vitamin E esters, particularly vitamin E acetate, were also shown to be promising agents in reducing UV-induced skin damage (Beijersbergen van Henegouwen et Bissett et al, 1990;Burke et al, 2000;Jurkiewicz et al, 1995;Record et al, 1991;Schoonderwoerd et al, 1991;Trevithick et al, , 1992. However, their photoprotective effects appear to be less pronounced as compared to vitamin E; as a result, some studies failed to detect photoprotection provided by vitamin E esters.…”
Section: Photoprotection Provided By Vitamin Ementioning
confidence: 91%
“…Numerous topical studies have demonstrated that vitamin E application prior to ultraviolet exposure significantly reduces acute skin responses, such as erythema and edema, sunburn cell formation (Darr et al, 1996;Lin et al, 2003;Ritter et al, 1997), lipid peroxidation (Khettab et al, 1988;Lopez-Torres et al, 1998;Yuen and Halliday, 1997), DNA-adduct formation, immunosuppression (Gensler and Magdaleno, 1991;Yuen and Halliday, 1997), as well as UVA-induced binding of photosensitizers (Beijersbergen van Henegouwen et Schoonderwoerd et al, 1991) and chemiluminescence (Evelson et al, 1997). Chronic skin reactions due to prolonged UVB/UVA-exposure, such as skin wrinkling (Bissett et al, 1990(Bissett et al, , 1992(Bissett et al, , 1989Jurkiewicz et al, 1995), and skin tumor incidence (Bissett et al, 1990(Bissett et al, , 1992(Bissett et al, , 1989Burke et al, 2000;Gensler and Magdaleno, 1991) were also diminished by topical vitamin E formulations.…”
Section: Photoprotection Provided By Vitamin Ementioning
confidence: 98%
“…Vitamin E esters, particularly vitamin E acetate, were also shown to be promising agents in reducing ultraviolet radiation (UVR)‐induced skin damage 27,28,32–34,36–38 . However, their photoprotective effects appear to be less pronounced compared with vitamin E; as a result, some studies failed to detect photoprotection provided by vitamin E esters.…”
Section: Photoprotection Provided By Vitamin Ementioning
confidence: 99%
“…The largest body of scientific evidence for a beneficial role of topical vitamin E exists for photoprotection ( Table 2). Numerous topical studies have demonstrated that vitamin E application prior to UV exposure significantly reduces acute skin responses, such as erythema and edema, sun- burn cell formation, [20][21][22] lipid peroxidation, [23][24][25] deoxyribonucleic acid (DNA) adduct formation, immunosuppression, 24,26 and ultraviolet A (UVA)-induced binding of pho-tosensitizers 27,28 and chemiluminescence. 29 Chronic skin reactions owing to prolonged ultraviolet B (UVB) or UVA exposure, such as skin wrinkling, [30][31][32][33] and skin tumor inci- 35 Together with other studies, 25 this work suggests that topically applied vitamin E has the potential to penetrate into dermal layers, where oxidative stress occurs, 19 and thus protects against photoaging.…”
Section: Photoprotection Provided By Vitamin Ementioning
confidence: 99%
“…An additional 15 animal studies have consistently found topical pretreatment with vitamin E photoprotective using variety of outcome measures including erythema, lipid peroxidation, wrinkling and sunburn cell formation [42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]. …”
Section: α-Tocopherolmentioning
confidence: 99%